2020
DOI: 10.3390/ani10112107
|View full text |Cite
|
Sign up to set email alerts
|

Role of the JAK-STAT Pathway in Bovine Mastitis and Milk Production

Abstract: The cytokine-activated Janus kinase (JAK)—signal transducer and activator of transcription (STAT) pathway is a sequence of communications between proteins in a cell, and it is associated with various processes such as cell division, apoptosis, mammary gland development, lactation, anti-inflammation, and immunity. The pathway is involved in transferring information from receptors on the cell surface to the cell nucleus, resulting in the regulation of genes through transcription. The Janus kinase 2 (JAK2), signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 131 publications
1
27
0
1
Order By: Relevance
“…SOCS2 inhibits the GH/IGF-1 axis and negatively regulates growth and development after birth [ 60 , 61 ], whereas SOCS3 inhibits the EPO signaling pathways [ 62 ]. Moreover, previous studies report a close association between the signaling pathways and the lactation regulatory factors [ 63 , 64 ]. This study analyzed the expression and protein levels of SOCS2 and SOCS3 genes to decipher their involvement in the expression of milk protein and fat synthesis-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS2 inhibits the GH/IGF-1 axis and negatively regulates growth and development after birth [ 60 , 61 ], whereas SOCS3 inhibits the EPO signaling pathways [ 62 ]. Moreover, previous studies report a close association between the signaling pathways and the lactation regulatory factors [ 63 , 64 ]. This study analyzed the expression and protein levels of SOCS2 and SOCS3 genes to decipher their involvement in the expression of milk protein and fat synthesis-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhao et al (58) found that lncRNA UCA1 could accelerate cell viability, block apoptosis and function as competitive endogenous RNA (ceRNA) to target TLR4 by sponging miR-499b-5p, thereby alleviating the LPS-challenged cell damage. Based on above results, it was speculated that these DElncRNAs are likely involved in regulating the process of bovine mastitis via their immune-related target genes (7,(59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 97%
“…Key proteins in the cAMP, PI3K-Akt, Prolactin, and Ras pathways and PPI networks obtained from KEGG pathway enrichment analysis interact with each other to form a complex target−pathway network. For example, the downstream proteins of the Prolactin pathway are JAK2, MAPK, and SRC and regulate apoptosis and inflammation through the JAK/STAT pathway [61][62][63]. MAPK integrates crosstalk with multiple signaling pathways, such as the Ras/MAPK pathway, ErbB pathway, and PI3K-Akt pathway.…”
Section: Discussionmentioning
confidence: 99%